Apatite, allanite, titanite and monazite characteristics in S-, I- A-type Cape Granites - Spicer, Esme M. (Esme Marelien) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2001.